(untitled) (International Journal of Applied Research in Management and Economics, 2021)
In the era of the digital revolution, organizations are surrounded by disruptive technologies and find themselves constantly in the middle of change processes. In recent years, blockchain technology has evolved tremendously, and in the future, it may fundamentally influence and change the finance and accounting domain of the early 21st century. Originally the blockchain technology was created only as technology to introduce the cryptocurrency Bitcoin, however by now the blockchain is considered by experts as a major innovation beyond its initial scope. In light of these changing circumstances, innovative opportunities, as well as new challenges, arise. This creates many questions and academic debates among researchers all over the globe as to which business models and functions in the financial sector may become obsolete or where to streamline and enhance processes through blockchain applications. The paper addresses the research question to what extent the blockchain technology is capable of changing well-known business processes and finance functions within companies. In doing so, it shows the opportunities and challenges, which are based on an extensive literature-review by the authors. The paper presents current use cases on market and finishes with an outlook on the future potential of blockchain.